Metrics for project management : formalized approaches - Rad, Parviz F., 1942-; Levin, Ginger (Vienna, VA : Management Concepts, 2006)
It describes a comprehensive set of project management metrics in an easy-to-read format, through a unique presentation of metrics through the categories of "things", "people" and "enterprise".
Includes bibliographical references (p. [357]-360) and index.
uaj 29/10/2013
Loans
Keywords: Project management -- Quality control; Performance standards; Work measurement